If f(x) = log2 (x - 2)3 and g(x) = log8 (x - 2), when is (f + g)(x) = 0?

working with logs base 2,

since 8=2^3, g(x) = 1/3 log(x-2)

(f+g)(x) = f(x)+g(x)
= 3log(x-2) + 1/3 log(x-2)
= 10/3 log(x-2)

so, if (f+g)(x) = 0,
log(x-2) = 0
x-2 = 1
x = 3

check

log_2(3-2)^3 = 0
log_8(3-2) = 0

Thanks Steve! I am starting to write these down so that way I will understand them. It is easier for me to go off an example. I appreciate all your help.

To find the value of x when (f + g)(x) = 0, we need to first express (f + g)(x) in terms of f(x) and g(x).

Given f(x) = log2 (x - 2)^3 and g(x) = log8 (x - 2), to find (f + g)(x), we can add the two functions together:

(f + g)(x) = log2 (x - 2)^3 + log8 (x - 2)

To simplify the expression, we can use the logarithmic property of addition:

log2 (x - 2)^3 + log8 (x - 2) = log2 [(x - 2)^3] + log2 (8^(1/3))

Next, we can apply the power rule of logarithms and simplify further:

log2 [(x - 2)^3] + log2 (8^(1/3)) = log2 [(x - 2)^3] + log2 (2)

Since log2 (2) = 1, we can simplify the expression even further:

log2 [(x - 2)^3] + log2 (2) = log2 [(x - 2)^3] + 1

So, (f + g)(x) = log2 [(x - 2)^3] + 1

Now, to find the value of x when (f + g)(x) = 0, we set the expression equal to zero:

log2 [(x - 2)^3] + 1 = 0

Subtracting 1 from both sides, we get:

log2 [(x - 2)^3] = -1

Using the logarithmic property of equality, we can rewrite it as:

2^(-1) = (x - 2)^3

Simplifying, we have:

1/2 = (x - 2)^3

Taking the cube root of both sides, we get:

∛(1/2) = x - 2

To find the value of ∛(1/2), we can calculate:

∛(1/2) ≈ 0.7937

Adding 2 to both sides, we find:

x ≈ 0.7937 + 2 ≈ 2.7937

Therefore, when (f + g)(x) = 0, x is approximately equal to 2.7937.